Four new species of the subgenus Pachylaelaps (Longipachylaelaps) from Italy, with a new identification key to the known species (Acari: Pachylaelapidae) - Mašán, Peter (Zootaxa, 2017)
The study presents descriptions of four new species of mites in the subgenus Pachylaelaps (Longipachylaelaps) Mašán, 2007 (Acari, Pachylaelapidae), based on females and males collected in forest habitats from the Bergamasque Alps and Prealps, Northern Italy. The new species are P. (L.) abludens sp. nov., P. (L.) bergomensis sp. nov., P. (L.) marcovallei sp. nov., and P. (L.) pantinii sp. nov. New species identification keys are provided for males and females.